2004
DOI: 10.1111/j.0022-202x.2004.23491.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Covalently Bound Ceramide Are Associated with Ultraviolet B-Induced Perturbation of the Skin Barrier

Abstract: Although ultraviolet B (UVB) irradiation perturbs the skin barrier, little is known about the mechanism(s) with respect to the metabolism of ceramide (Cer). We examined changes in intercellular lipids in murine stratum corneum following UVB irradiation. A single UVB (75 mJ per cm(2)) irradiation caused a significant increase in transepidermal water loss, which plateaued at day 4. In parallel, covalently bound Cer was significantly decreased with the greatest decrease at days 3-4. In contrast, the levels of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 44 publications
4
68
0
Order By: Relevance
“…These localization-dependent differences are probably influenced by the higher sun exposure of the face and neck. This presumption was confirmed by Liu et al [31], who showed that cumulative sun exposure does reduce SC hydration, probably due to a UVB-induced downregulation of epidermal ceramides, fillagrins and aquaporins [32,33,34,35]. …”
Section: Discussionmentioning
confidence: 73%
“…These localization-dependent differences are probably influenced by the higher sun exposure of the face and neck. This presumption was confirmed by Liu et al [31], who showed that cumulative sun exposure does reduce SC hydration, probably due to a UVB-induced downregulation of epidermal ceramides, fillagrins and aquaporins [32,33,34,35]. …”
Section: Discussionmentioning
confidence: 73%
“…Radiotherapy induced skin dermatitis exists in an acute and a chronic form [21,22]. In this study we use a high single radiation dose of 30 Gy in order to cause severe skin dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation-induced dermatitis represents one of the most important dose limiting factors in radiotherapy [21,22]. In the present study we are focusing on the acute form of radiotherapy induced skin dermatitis, which normally develops within a few weeks after exposure to a high dose of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a closer look at the result showed that the ratio of CER [EOH] to CER [AS] was slightly increased after UVB irradiation. This shows an interesting potential of UVB irradiation on improving the average Cer chain length, even at a dose known to disrupt the skin barrier [21]. Further studies to investigate the effectiveness of short-term suberythemal UVB on average CER chain length in AD patients are required.…”
Section: Positive Changes Of Epidermal Barrier Induced By Short-term mentioning
confidence: 91%
“…In addition, the highly upregulated sphingomyelin deacyclase may also cause a CER deficiency as a result of competition with β-GlcCerase and sphingomyelinase for their respective substrates, sphingomyelin and glucosylceramide [19]. Downregulation of the de novo synthesis of CER in AD [20], possibly due to the decreased expression of Serine Palmitoyltransferase (SPT) [21], may also account for the decreased CER in AD. There is also a reduced amount of ω-hydroxyceramide bound to the cornified envelope, also called covalently bound CER, possibly due to the reduced expression of involucrin in AD [18,20].…”
Section: Decreased Cer Decreased Covalently Bound Cer Decreased Invmentioning
confidence: 99%